Cat at home? Cat scratch disease with atypical presentations and aggressive radiological findings mimicking sarcoma, a potential diagnostic pitfall. (29th October 2021) - Amerstorfer, Florian; Igrec, Jasminka; Valentin, Thomas; Leithner, Andreas; Leitner, Lukas; Glehr, Mathias; Friesenbichler, Jörg; Brcic, Iva; Bergovec, Marko
Abstract : Background and purpose — Cat scratch disease (CSD) is a self-limiting disease caused by Bartonella (B.) henselae. It is characterized by granulomatous infection, most frequently involving lymph nodes. However, it can present with atypical symptoms including musculoskeletal manifestations, posing a diagnostic challenge. We describe the prevalence and demographics of CSD cases referred to a sarcoma center, and describe the radiological, histological, and molecular findings. Patients and methods — Our cohort comprised 10 patients, median age 27 years (12–74) with clinical and radiological findings suspicious of sarcoma. Results — 7 cases involved the upper extremities, and 1 case each involved the axilla, groin, and knee. B. hensela e was found in 6 cases tested using polymerase chain reaction and serology in 5 cases. 9 cases were soft tissue lesions and 1 lesion involved the bone. 1 patient had concomitant CSD with melanoma metastasis in enlarged axillary lymph nodes. On MRI, 5 soft tissue lesions were categorized as probably inflammatory. In 3 cases, with still detectable lymph node structure and absent or initial liquefaction, the differential diagnosis included lymph node metastasis. A sarcoma diagnosis was suggested in 4 cases. The MRI imaging features of the bone lesion were suspicious of a bone tumor or osteomyelitis. Interpretation — Atypical imaging findings cause a diagnostic challenge and the differential diagnosis includes malignant neoplasms (such as sarcoma or carcinoma metastasis) and other infections. The distinction between these possibilities is crucial for treatment and prognosis.